2022
DOI: 10.1186/s12913-021-07443-8
|View full text |Cite
|
Sign up to set email alerts
|

Two decades of regional trends in vaccination completion and coverage among children aged 12-23 months: an analysis of the Uganda Demographic Health Survey data from 1995 to 2016

Abstract: Background Childhood vaccination is an important public health intervention but there is limited information on coverage, trends, and determinants of vaccination completion in Uganda at the regional level. We examined trends in regional vaccination coverage and established the determinants of vaccination completion among children aged 12-23 months in Uganda. Methods We analyzed data from the women’s questionnaire for the 1995-2016 Uganda Demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…From 2000 to 2016, improvements in vaccine delivery increased equity and shifted the dominant contribution to inequity from largely supply-side constraints to demand-side constraints, where the households' behaviour, whether guided by nancial and social constraints, awareness, or beliefs, seems to play a stronger role in immunization. Our ndings are consistent with the ndings from two other studies conducted in Uganda and Ethiopia that reported that maternal education, wealth status, region of residence, and the household head's sex were strongly associated with full vaccination coverage (Geweniger & Abbas, 2020;Okello et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…From 2000 to 2016, improvements in vaccine delivery increased equity and shifted the dominant contribution to inequity from largely supply-side constraints to demand-side constraints, where the households' behaviour, whether guided by nancial and social constraints, awareness, or beliefs, seems to play a stronger role in immunization. Our ndings are consistent with the ndings from two other studies conducted in Uganda and Ethiopia that reported that maternal education, wealth status, region of residence, and the household head's sex were strongly associated with full vaccination coverage (Geweniger & Abbas, 2020;Okello et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Table 1 summarizes the e ciency (coverage) and equity metrics (concentration indices and absolute equity gap) for 2000and 2016. Additional data for 2000, 2006, and 2016 is featured in Tables 1 to 4 in the supplementary material, and subnational data in tables 5 to 16. Figure 1 shows the coverage and equity by region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 In 2020, a report in Lango sub-region in northern Uganda indicated low vaccination coverage (close to 50% of children immunized which is lower than the national average of 55%). 10 In the same year, a study in Lira showed that 49%, 3%, and 48.7% of children had received a pentavalent and measles-containing vaccine respectively by 1 year which was lower than the national target of 90%. 11 However, there is scarce information on the predictors of adherence to routine immunization schedules among caretakers in Lira city, thus the present study.…”
Section: Introductionmentioning
confidence: 97%
“…Despite the importance of these cards, they are sometimes not retained until the recommended age, or they are lost or damaged [ 21 ]. In previous studies in Uganda, the possession of a UCHC was associated with childhood vaccination completion [ 22 ].…”
Section: Introductionmentioning
confidence: 99%